ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA KOPERASI SIMPAN PINJAM TANAOBA LAIS MANEKAT - Ona Silfia Liunima; Petrus E de Rozari; Wehelmina M Ndoen (Journal of Management Small and Medium Enterprises (SMEs), 2019)
This research is done in Tanaoba Lais Manekat cooperative. The purpose of this research is to know the source and using of working capital as well as its influence on the profitability of Tanaoba Lais Menekat cooperatives. The study used a quantitative descriptive approach with guidance on cooperative financial statements during the research period of 2013 – 2017. The analysis of the data used in this study is the analysis of the source and the using of working capital by comparing the two-year consectively financial report and profitability analysis with return on asset ratio and return on aquity ratio. Results showed that there was fluctuations in the development of sources and capital use as well as profitability and no working capital relationship to the profitability of Tanaoba Lais Manekat cooperatives. Keywords : Working Capital, Profitability, Return On Asset, Return On Equity, Source of Working Capital